CTA Project Completion Report: Hello Tractor - Koutchade, Folake; Lohento, Ken (Technical Centre for Agricultural and Rural Cooperation, 2020)
This project was launched following a call for proposals on information and communication technology (ICT)-enabled mechanisation that CTA launched to support activities of its ICT programme in particular and identify how digital innovations could support mechanisation and youth jobs. The winning proposal selected was the project “Connecting Smallholder Farmers to Tractors Powered by Hello Tractor”. Knowledge has been generated to inform CTA’s programme of activities and stakeholders about digitalisation opportunities to support mechanisation and create jobs for youth.